A New Long Noncoding RNA ALB Regulates Autophagy by Enhancing the Transformation of LC3BI to LC3BII during Human Lens Development - Qiuli Fu; Zhenwei Qin; Lifang Zhang; Danni Lyu; Qiaomei Tang; Houfa Yin; Zhijian Chen; Ke Yao (Elsevier, 2017)
Autophagy is essential in lens organelle degradation. This study aimed to seek potential autophagy-associated long noncoding RNAs (lncRNAs) and their relative mechanisms in human lens development using the "fried egg" lentoid body (LB) generation system. The expression pattern of LC3B in differentiating LBs was similar to that in developing a mouse lens in vivo. Among the massive lncRNAs expressed with a significant difference between induced pluripotent stem cells (iPSCs) and LBs, lncRNA affecting LC3B (ALB), which was predicted to have a co-relationship with the autophagy marker LC3B, was highly expressed in differentiating lens fibers in LBs. This result was consistent with its high expression in human embryonic lenses compared to those in embryonic stem cells (ESCs). Furthermore, lncRNA ALB knockdown resulted in the downregulation of LC3BII at the protein level, therefore inhibiting the autophagy process in human lens epithelial cells (HLECs). Our results identify lncRNA ALB, a potential autophagy regulator in organelle degradation during human lens development, highlighting the importance of lncRNAs in lens development.